2001
DOI: 10.1149/1.1339036
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Polyaniline in Nonaqueous Electrolyte and Its Evaluation as Electrode Material for Electrochemical Supercapacitors

Abstract: In this study, the performance of a polyaniline (PANI) based supercapacitor where electroactive PANI films were prepared on carbon paper electrodes from a nonaqueous solution with an organic acid (CF 3 COOH) as the proton source was investigated. The use of nonaqueous media as electrolyte led to an increase of the electroactivity window from 0.75 V in aqueous media up to 1.0 V. Low frequency capacitance, evaluated by electrochemical impedance spectroscopy, of about 150 F/g is reported. Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(137 citation statements)
references
References 30 publications
8
128
1
Order By: Relevance
“…Regarding the composites, it can be observed that those prepared by mechanical mixing with polyaniline (samples AM) and after aniline polymerisation over the thermally [14,21,24,26]. Moreover, as the amount of polyaniline increases (AM3 sample), a noticeable change in the voltammogram shape appears.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the composites, it can be observed that those prepared by mechanical mixing with polyaniline (samples AM) and after aniline polymerisation over the thermally [14,21,24,26]. Moreover, as the amount of polyaniline increases (AM3 sample), a noticeable change in the voltammogram shape appears.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%
“…Moreover, as the amount of polyaniline increases (AM3 sample), a noticeable change in the voltammogram shape appears. This change in the voltammogram is more marked for pure polyaniline and it is attributed to limited ions diffusion-migration process in the bulk of the polymer and to the ohmic drop within the thick polymer layer [26]. The integration of the curves, taking into account the scan rate and the double layer contribution has allowed us to estimate the ratio charge-to-mass for chemically polymerised polyaniline.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…9 presents the repeated cycles of charge-discharge in the time span of 2500 s. No shape and size changes were observed pointing to the reversibility as well as the stability of the system. The specific capacitances of the electrodes are evaluated 23,24) using:…”
Section: )mentioning
confidence: 99%
“…Zinc is widely used as a negative electrode material of batteries (such as Zn-Mn and Zn-Ag batteries) owing to the advantages of low equilibrium potential, high specific energy density, being an abundant resource, having low cost, and being environmentally friendly [3]. Conducting polymer polyaniline (PANI) [4,5] has attracted researchers' interest as a cathode active material of rechargeable batteries in aqueous [6][7][8] and non-aqueous electrolytes [9][10][11][12] (such as Zn-PANI secondary battery [13][14][15][16][17] and Li-PANI secondary battery [18][19][20]). A significant portion of these studies has been devoted to PANI that exhibit excellent electrochemical activity and environmental stability.…”
Section: Introductionmentioning
confidence: 99%